Evidence for intergranular tunnelling in polyaniline passivated alpha-Fe nanoparticles - Sunny, Vijutha; Narayanan, T. N.; Sajeev, U. S.; Joy, Pattayil Alias; Kumar, D. Sakthi; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Nanotechnology, 2006)
Nanoparticles are of immense importance both from the fundamental and application points of view. They exhibit quantum size effects which are manifested in their improved magnetic and electric properties. Mechanical attrition by high energy ball milling (HEBM) is a top down process for producing fine particles. However, fineness is associated with high surface area and hence is prone to oxidation which has a detrimental effect on the useful properties of these materials. Passivation of nanoparticles is known to inhibit surface oxidation. At the same time, coating polymer film on inorganic materials modifies the surface properties drastically. In this work a modified set-up consisting of an RF plasma polymerization technique is employed to coat a thin layer of a polymer film on Fe nanoparticles produced by HEBM. Ball-milled particles having different particle size ranges are coated with polyaniline. Their electrical properties are investigated by measuring the dc conductivity in the temperature range 10-300 K. The low temperature dc conductivity (I-V) exhibited nonlinearity. This nonlinearity observed is explained on the basis of the critical path model. There is clear-cut evidence for the occurrence of intergranular tunnelling. The results are presented here in this paper.

Flexible microwave absorber based on nickel ferrite nanocomposite - Sunny, Vijutha; Kurian, Philip; Mohanan, P.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Alloys and Compounds, 2010)
Flexible magnetic composite materials were prepared by incorporating precharacterized nickel ferrite nanoparticles in a natural rubber matrix. The complex dielectric permittivity and magnetic permeability of the composites were measured at different microwave frequencies using the cavity perturbation technique. A steady increase in dielectric permittivity was observed with increase in filler concentration. Maxwell-Garnett mixture equations were employed to model the effective permittivity and permeability of the composite. Reflection loss was estimated by employing the model of single layer absorber backed with a perfect conductor. Reflection loss minima of -5.9 dB at 3.2 GHz for 12 mm thick rubber ferrite composite sheet is obtained in the S-band while a loss up to -16 dB could be achieved at 9.5 GHz in the X-band. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cavity perturbation; Complex permeability; Complex permittivity; Microwave absorber; Nanocomposites; Nickel ferrite

Synthesis of bio-compatible SPION-based aqueous ferrofluids and evaluation of radiofrequency power loss for magnetic hyperthermia - Mary, Antony P. Reena; Narayanan, T. N.; Sunny, Vijutha; Sakthikumar, D.; Yoshida, Yasuhiko; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Nanoscale Research Letters, 2010)
Bio-compatible magnetic fluids having high saturation magnetization find immense applications in various biomedical fields. Aqueous ferrofluids of superparamagnetic iron oxide nanoparticles with narrow size distribution, high shelf life and good stability is realized by controlled chemical co-precipitation process. The crystal structure is verified by X-ray diffraction technique. Particle sizes are evaluated by employing Transmission electron microscopy. Room temperature and low-temperature magnetic measurements were carried out with Superconducting Quantum Interference Device. The fluid exhibits good magnetic response even at very high dilution (6.28 mg/cc). This is an advantage for biomedical applications, since only a small amount of iron is to be metabolised by body organs. Magnetic field induced transmission measurements carried out at photon energy of diode laser (670 nm) exhibited excellent linear dichroism. Based on the structural and magnetic measurements, the power loss for the magnetic nanoparticles under study is evaluated over a range of radiofrequencies.
Keywords: Magnetic heating; Magnetic hyperthermia; Magnetic relaxation; Power loss; Superparamagnetism

Flexible microwave absorbers based on barium hexaferrite, carbon black, and nitrile rubber for 2-12 GHz applications - Vinayasree, S.; Soloman, M. A.; Sunny, Vijutha; Mohanan, P.; Kurian, Philip; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Applied Physics, 2014)
Flexile single layer electromagnetic wave absorbers were designed by incorporating appropriate amounts of carbon black in a nitrile butadiene rubber matrix along with an optimized amount of magnetic counterpart, namely, barium hexaferrite for applications in S, C, and X-bands. Effective dielectric permittivity and magnetic permeability were measured using cavity perturbation method in the frequency range of 2-12 GHz. The microwave absorbing characteristics of the composites were studied in the S, C, and X-bands employing a model in which an electromagnetic wave is incident normally on a metal terminated single layer. Reflection loss exceeding -20 dB is obtained for all the samples in a wide frequency range of 2-12 GHz when an appropriate absorber thickness between 5 and 9 mm is chosen. The impact of carbon black is clearly observed in the optimized composites on the mechanical strength, thickness, band width of absorption, dielectric properties, and absorptivity. (C) 2014 AIP Publishing LLC.